(untitled) (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2024)
Sri Lankan traditional medical system comprises many medicinal foods used to manage diabetes mellitus, dyslipidemia, and hypertension. Utilization of evidence-based knowledge of these foods in Western medical care needs acceptance of these medicinal foods by Western doctors. This survey was conducted as a descriptive cross-sectional knowledge, attitude, and practice of medicinal foods on MBBS-qualified doctors. The sample of 713 doctors was selected using a multistage cluster sampling technique, and data were collected using a validated, self-administered, structured questionnaire. Data were analyzed using the Statistical Software for Social Sciences – SPSS (version 21). The results revealed that the most doctors did not have satisfactory knowledge (SK) of these medicinal foods, positive attitudes (PA) towards prescribing them in Western practice, and good practice (GP) of prescription them for their patients. Social media and university education were the most prominent modes of acquiring medicinal food knowledge by doctors. Significantly (p< 0.05) different SK, PA, and GP levels of medicinal foods were observed in doctors of different ethnic and religious groups. Rural area exposure and rural school education showed significantly (p< 0.05) higher SK, PA, and GP levels. Doctors with satisfactory knowledge were more likely (OR 34;95%CI) to prescribe medicinal foods than those with poor knowledge. It was concluded that, any attempt to utilize the evidence-based knowledge of medicinal foods of traditional medicine in Western practice should focus first on improving the medicinal food knowledge of Western doctors. The development of an e-module on medicinal foods accessible via mobile phones and the inclusion of a short module on medicinal foods into medical student’s curriculum are recommended.